SPEECH ECOLOGY OF EDUCATION SEEKERS: THEORETICAL AND PRACTICAL ASPECTS - Bilavych, Halyna; Perchyk Marіana; Pavlyuk, Angelina; Ozarko, Veronika (Mountain School of Ukrainian Carpaty, 2021)
The article is devoted to theoretical and practical aspects of the problem of speech ecology of education seekers. It is noted that the issue of formation of speech culture is the subject of special attention of Ukrainian scientists. Тhe problem of speech ecology of education seekers is extremely relevant today: language is a necessary condition for the education of socially active, spiritually rich and morally developed personality. The professional success of an individual also depends on their speechmaking. According to research results, students have a medium and low level of mastery of speech culture. The Ukrainian language is of great importance in the education system, because it is with the help of the language in secondary and high school that education seekers acquire their competencies. Fluency in the Ukrainian language is the duty and prerogative of the future primary school teacher. Creating an ecological language environment in an educational institution is one of the pedagogical conditions for the formation of ecological Ukrainian speech of pupils and students. The scientific circle "Language Ecologists", whose task is to become a means of language activity aimed at purifying the speech environment from language errors, etc. In this way, both students and schoolchildren master all the necessary language and speech competencies, enrich their vocabulary and make the environment healthier.